Pregnenolone rescues schizophrenia-like behavior in dopamine transporter knockout mice. - Peiyan Wong (Public Library of Science (PLoS), 2012)
Pregnenolone belongs to a class of endogenous neurosteroids in the central nervous system (CNS), which has been suggested to enhance cognitive functions through GABA(A) receptor signaling by its metabolites. It has been shown that the level of pregnenolone is altered in certain brain areas of schizophrenic patients, and clozapine enhances pregnenolone in the CNS in rats, suggesting that pregnenolone could be used to treat certain symptoms of schizophrenia. In addition, early phase proof-of-concept clinical trials have indicated that pregnenolone is effective in reducing the negative symptoms and cognitive deficits of schizophrenia patients. Here, we evaluate the actions of pregnenolone on a mouse model for schizophrenia, the dopamine transporter knockout mouse (DAT KO). DAT KO mice mirror certain symptoms evident in patients with schizophrenia, such as the psychomotor agitation, stereotypy, deficits of prepulse inhibition and cognitive impairments. Following acute treatment, pregnenolone was found to reduce the hyperlocomotion, stereotypic bouts and pre-pulse inhibition (PPI) deficits in DAT KO mice in a dose-dependent manner. At 60 mg/kg of pregnenolone, there were no significant differences in locomotor activities and stereotypy between wild-type and DAT KO mice. Similarly, acute treatment of 60 mg/kg of pregnenolone fully rescued PPI deficits of DAT KO mice. Following chronic treatment with pregnenolone at 60 mg/kg, the cognitive deficits of DAT KO mice were rescued in the paradigms of novel object recognition test and social transmission of food preference test. Pregnenolone thus holds promise as a therapeutic candidate in schizophrenia.